Development of Pop-Up Book Media Based on Heroic Values in Madrasah Ibtidaiyah - Sholiha, Diniyah Mar’atus; Karim, Abdul; Agoro, Samira (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
The lack of engaging learning materials in Madrasah Ibtidaiyah triggers the need for innovative methods, such as pop-up books, to teach the values of heroism effectively and ensure technology accessibility. This research aims to develop innovative learning media in the form of a Pop-Up Book based on heroic values for Madrasah Ibtidaiyah (MI) students. The method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation and evaluation. The research results show that the Pop-Up Book media developed is valid and suitable for use in learning with a validity level of 88%. Implementation on 13 class V students at MI Nurul Hidayah Prajekan Bondowoso showed a positive response with an acceptance rate of 86.15%. This media not only increases students' interest and understanding of the subject matter, but is also effective in instilling moral values such as courage, sacrifice and patriotism. Teacher training in the use of this media is very necessary to optimize its use in the learning process. This study's contribution lies in the development and validation of Pop-Up Book media, which shows its effectiveness in increasing students' interest in and understanding of heroic values. This study highlights the importance of teacher training for optimal media use, providing evidence that this visual and interactive learning approach can strengthen character education in Madrasah Ibtidaiyah. Further research is recommended to develop other moral value-based learning media and evaluate the long-term impact of using Pop-Up Book media on student character formation.